Design and development of a low-voltage DC domestic power supply system - Van der Merwe, Cornelius J. (Bloemfontein : Central University of Technology, Free State, 2018)
Much effort is spent in regulating the power quality in alternating current power supplies for electronic devices. Many electronic devices, however, do not use alternating current, but rather direct current. The output of most small scale renewable energy systems are also direct current, so it can be connected to the loads more efficiently by eliminating the inverter stage. In a circuit with a number of rectification stages the conversion losses can add up to a significant amount. By reducing the number of conversion stages or possibly eliminating some of the stages the overall system could be more efficient. The purpose of this dissertation is to present the simulation design and results of a direct current distribution system, containing common household appliances connected to a direct current grid supply and a renewable energy source. A bottom-up design approach is used where a list of household appliances with their voltage needs is identified and the distribution voltage is then selected based on the voltage needs. The distribution system is modelled using Matlab and Simulink software. Results show that common household loads can be supplied directly with direct current, from either a main direct current grid supply, or a renewable energy system with direct current output. This direct current distribution system is compared to two other systems: (1) Existing alternating current system and (2) Hybrid system (converting alternating current to direct current for distribution in the house). The three systems are compared to each other in terms of power efficiency and material cost. The existing alternating current system is shown to be the most efficient, with an average power efficiency of 87.85 %. The second most efficient system is the hybrid system with average power efficiency of 86.95 %, and the least efficient of the three is the direct current distribution system with 86.45 %. The main reason why the direct current system is less efficient is because of the high input power of the microwave oven when connected to a direct current supply. The direct current system is more efficient than the alternating current system if the microwave oven load is taken out of both. Future work will involve more detailed operational and transient state simulations of the loads in the direct current system. Another recommendation is to find a direct current design for supplying the microwave oven load that does not incur large losses. A final recommendation is to build a practical test set-up of the direct current system in order to analyse the practical aspects of a residential direct current distribution system.
Thesis (Master of Engineering (Electrical)) -- Central University of Technology, Free State, 2018
Keywords: Central University of Technology, Free State -- Dissertations; Electric power transmission -- Direct current; Power resources; Renewable energy sources